1988
DOI: 10.1111/j.1471-4159.1988.tb02490.x
|View full text |Cite
|
Sign up to set email alerts
|

GABAA Receptor Populations Bind Agonists and Antagonists Differentially and with Opposite Affinities

Abstract: Pretreatment of synaptosomal membranes with a diazo-coupling reagent and the presence of Cl- ions were used to differentiate high- and low-affinity populations of postsynaptic gamma-aminobutyric acid (GABAA) receptors. The super-low-affinity GABAA receptors were characterized by the enhancing effect of GABA on [3H]diazepam binding. The GABA antagonists 2-(3-carboxypropyl)-3-amino-4-methyl-6-phenylpyridazinium chloride (SR 95103) and 3-alpha-hydroxy-16-imino-5 beta-17-aza-androstan-11-one (R 5135) shifted and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1989
1989
1997
1997

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…It has also been demonstrated that other compounds that have detergent activity, such as lysophosphatidylcholine and digitonin, increase [3H]muscimol binding (Ito and Kuriyama, 1982). Thus the decrease in r3H]SR 95531 binding as well as the increase in the binding of [3Hlmuscimol induced by lysophosphatidylcholine treatment possibly antagonist-preferring binding sites (Maksay, 1988;Olsen and Snowman, 1983). Our results support this hypothesis, since the low-affinity binding site of r3H1SR 95531 seems to be responsible for the antagonistic action of SR 95531 in GABA receptor-gated C1-flux.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It has also been demonstrated that other compounds that have detergent activity, such as lysophosphatidylcholine and digitonin, increase [3H]muscimol binding (Ito and Kuriyama, 1982). Thus the decrease in r3H]SR 95531 binding as well as the increase in the binding of [3Hlmuscimol induced by lysophosphatidylcholine treatment possibly antagonist-preferring binding sites (Maksay, 1988;Olsen and Snowman, 1983). Our results support this hypothesis, since the low-affinity binding site of r3H1SR 95531 seems to be responsible for the antagonistic action of SR 95531 in GABA receptor-gated C1-flux.…”
Section: Discussionmentioning
confidence: 97%
“…It has been suggested that antagonists interact not only with GABA recognition sites, but also hydrophobic accessory sites (Maksay and Ticku, 1984). Earlier reports also suggested that the antagonists interacted competitively with high-affinity GABA sites, and not competitively with lower-affinity sites due to preferential interaction with hydrophobic sites (Maksay, 1988). As a consequence of PLase A, cleavage of membrane phospholipids, unsaturated free fatty acids and lysosphospholipids are released.…”
Section: Discussionmentioning
confidence: 99%
“…findings of others that bicuculline acts as a noncompetitive antagonist of low affinity (functional) GABAA receptors in the brain (for review see Maksay, 1988), although Riesz & Erdö (1985) reported occasional reversal of bicuculline-induced contractions by muscimol. In contrast to direct effects on uterine motility mediated via GABAA receptors, the GABAB receptor-mediated uterine excitation may be indirect or may ensue from metabolic factors, as it occurs after a delay of about 1 -8 min both for GABA and baclofen.…”
Section: Pharmacological Characterization Of Uterine Contractionsmentioning
confidence: 99%
“…The high-affinity GABAA agonist [3H]muscimol has been successfully used in dissociation studies, even at physiological temperature (Yang and Olsen, 1987). Dissociation studies were extended here to the new GABAA antagonist [ 3H]2-( 3-carboxypropyl)-3-amino-6-p-methoxyphenylpyndazinium bromide ([3H]SR 95531) (Heaulme et al, 1987) which has preferential affinity to the lower affinity GABAA binding sites (Maksay, 1988;McCabe et al, 1988).…”
mentioning
confidence: 99%